Report of Visit to Spain, Autumn, 1947 (1947)
1947 038-0010-001 Confidential. REPORT OF VISIT TO SPAIN, AUTUMN, 1947. Having recently visited many Spanish workers' homes scattered over the two large provinces of Northern Spain, i.e. Guipuzcoa and Viscaya — including the industrial area of Bilbao, Baracaldo and Sestao, I feel myself under a deep obligation to pass on particulars of the very savage sentences passed on political opponents of the Franco regime. There is nothing new in the over-all picture I describe — they add just one little bit more to the overwhelming evidence of the frightful oppression of Franco's political opponents coming from almost every visitor to Spain and confirmed by such reports as that given by the "Times" correspondent in its issue of Jan. 10th last — giving particulars of the brutal sentences upon the 16 Socialists at the court-martial at Ocano — whose "crime" was that they had tried to restart the Socialist Party. All were known to be anti-communist — well known democrats who had given many years' service to the Socialist and Trade Union movement. James Oldfield, the "Daily Herald" correspondent, it will be remembered, reported upon one whom he had known intimately for at least two years, described as a moderate Socialist - opposed to Communism — and sentenced to 15 years. My information, gathered in each case from first-hand sources, is of men who have served the whole or part of their sentences, whom I have personally interviewed, some of them badly beaten up in prison — one had his teeth knocked out — and released only when their health had completely broken down. One poor fellow I visited was almost too weak to speak. They sent for me as they knew of my visit, and he was asking for news of his two children, who had been under my care here in England — one of whom had volunteered as a W.A.A.F. and had been stationed at an R.A.F. station in Yorkshire during the blitz, and has since married one of our sergeant-pilots. I had news three weeks after I left Spain that he had died ten days after my last visit to him. Others who had also only been released when extremely weak, had never and it appears from all they knew would never be able to work again. The daughter of one of them wrote me a few weeks ago to say her father, too, was dying. In another case the father was shot (recently). I learned this from the son — and his mother and the wives of other men who had been executed demonstrated outside the prison in their anger, and it appears that the authorities, fearing a riot, gave orders for the crowd to be fired upon. The boy's mother was wounded by a bullet, from which she has since died. That lad is now in England. He came as a stowaway. I had to appear at the South-Western Police Court in connection with his case. I am glad to say that after we had been able to provide the Home Secretary with corroboratory evidence he was given permission to stay. Of seventeen homes I visited, no less than the fathers of ten of these families had served from two to five years. Two had been executed, one died as result of prison experiences, another on his death bed. One of the men who had been executed (a friend of Prieto's) was the father of a Basque girl who came here when 14 years of age as a Basque refugee under my care at Reigate. She later served as a nurse at the Queen Elizabeth's Hospital in London through the latter part of the War. She and her husband, Capt. R. J. Turner, D.S.O., can confirm much of the foregoing, as 292/946/38/10(I)